Transformasi Sistem Informasi Persediaan Mobil Bekas Ke Platform Mobile: Studi Kasus Showroom Auto88group - Wandi Aprianto (METIK JURNAL, 2024)
This study aims to design and develop a mobile-based used car inventory information system for the Auto88Group showroom. This system is designed to facilitate the management of car stock data, sales, and inventory reports in real-time and efficiently via mobile devices. The system development uses the Agile method, which allows iterative development. This system is built using Flutter to support Android and iOS platforms, with MySQL database integration. Based on the implementation results, this system increases inventory management efficiency by up to 30%, allows real-time access to stock information, and speeds up the transaction process.